Embracing Complexity : A Conversation with David Cannadine. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and eminent historian David Cannadine, Princeton University. This thoughtful conversation includes an examination of different aspects of the societal role of both history and historians while rejecting the simplifying distortions of the historical record that we are regularly presented with. David also provides behind-the-scenes insights into several of his bestselling books, including The Undivided Past: Humanity Beyond Our Differences.This carefully-edited book includes an introduction, Imposing Order, and questions.